Encountering the sacred : the debate on Christian pilgrimage in late antiquity - Bitton-Ashkelony, Bruria (Transformation of the classical heritage, 2005)
This innovative study sheds new light on one of the most spectacular changes to occur in late antiquity--the rise of pilgrimage all over the Christian world--by setting the phenomenon against the wide background of the political and theological debates of the time.